Rational design : a high-throughput computational screening and experimental validation methodology for lead-free and emergent hybrid perovskites - Chakraborty, Sudip (2020)
Perovskite solar cells, with efficiencies of 22.1%, are the only solution-processable technology to outperform multicrystalline silicon and thin-film solar cells. Whereas substantial progress has been made in scalability and stability, toxicity concerns drive the need for lead replacement, intensifying research into the broad palette of elemental substitutions, solid solutions, and multidimensional structures. Perovskites have gone from comprising three to more than eight (CH3NH3, HC(NH2)2, Cs, Rb, Pb, Sn, I, Br) organic and inorganic constituents, and a variety of new embodiments including layered, double perovskites, and metal-deficient perovskites are being explored. Although most experimentation is guided by intuition and trial-and-error-based Edisonian approaches, rational strategies underpinned by computational screening and targeted experimental validation are emerging. In addressing emergent perovskites, this perspective discusses the rational design methodology leveraging density functional theory-based high-throughput computational screening coupled to downselection strategies to accelerate the discovery of materials and industrialization of perovskite solar cells.